Computational fluid dynamics simulation of internal fluid flow: A case of venturi effect / Kho Tuck Sing - Kho, Tuck Sing (2021)
This research project uses the Ansys Fluent software to conduct various Computational Fluid Dynamics (CFD) simulation of venturi effect occurs in an internal pipe flow based on the multi-phase flow model. In fluid dynamics, venturi effect is a common phenomenon occurs in an internal pipe flow, where a reduction in fluid pressure resultant from a fluid flow through a constricted section of a pipe. In accordance to Bernoulli's principle, an incompressible fluid's velocity increases as it passes through a constriction, in accordance to the principle of mass continuity, while its static pressure must decrease in accordance to the principle of conservation of mechanical energy. Hence, any gain in kinetic energy a fluid may attain by its increased velocity through a constriction is balanced by a drop in pressure. Physical experiments are time consuming and definitely will not be cost-effective to study the venturi-effect occurs within the pipelines. Therefore, CFD simulation is proposed to simulate the venturi effect occurs in an air ejector in this research project. Initially, a 2-D geometry modelling of the preliminary designed air ejector with water inlet, air inlet, converging section, throttling section, diverging section and outlet is constructed, conditioned, simulated and analyzed. The design and simulation process will be repeated to further improve the hydraulic conditions by modification of pre- and post-venturi effect piping arrangements. All simulation results will be plotted and analyzed from the pressure, velocity and volume fraction perspectives. Hypothetically, a streamline flow will enhance the hydraulic conditions and the mixing quality in this research project, through analyzing the simulation results of various improvement.